A revision of distribution and historical analysis of preferred hosts of Orobanche ramosa (Orobanchaceae) in Poland - Renata Piwowarczyk (Acta Agrobotanica, 2012)
The Polish localities of Orobanche ramosa L., branched broomrape, are either extinct or have not been confirmed for many years. This paper presents two new localities of O. ramosa in Poland from the Płaskowyż Proszowicki plateau (Wyżyna Małopolska upland) and the Nizina Nadwiślańska lowland (Kotlina Sandomierska basin). Habitat preferences and the abundance at the sites are described. A revised map of the distribution and a historical analysis of preferred hosts in Poland are included. The taxonomy, biology, ecology and control methods of O. ramosa are also discussed.